Hubungan Pemberian Asi Ekslusif dengan Kejadian Stunting pada Baduta 24-59 Bulan di Puskesmas Cempaka Putih Jakarta Pusat - Juli Mulyani Putri; Roza Indra Yeni (Jurnal Kesehatan Amanah, 2025)
Stunting is a growth and development disorder in children based on length or height according to age that is less than -2 standard deviations (SD) on the World Health Organization (WHO) growth curve which occurs due to poor nutrition, lack of exclusive breastfeeding, recurrent infections and psychosocial stimulation. which is insufficient. This research aims to identify the relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 24-59 months at the Cempaka Putih District Health Center, Central Jakarta. This research design uses a quantitative correlation approach with a cross-sectional design. with a population of 1075 respondents and a sample of 91 respondents. Sampling used simple random sampling. The research instrument used an exclusive breastfeeding questionnaire with 12 question items and used an anthropometric TB/U measuring tool using Microtoice. Data were tested using chi square (⍺ = 0.05). The results of the research show that there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 24-59 months at the Cempaka Putih District Health Center, Central Jakarta. with significance value = 0.000 < 0.05. Nurses are expected to be able to help mothers prevent stunting in their children through education about nutrition and health of toddlers in order to reduce the number of stunted toddlers. For future researchers, they should examine other variables related to the incidence of stunting in toddlers aged 24-59 months, such as nutritional and economic status of the family and others.